Classification of topography using dem data and its correlation with the geology of Greece - Kyriakidis, Phaedon; Zargli, Eleni; Liodakis, Stelios; Savvaidis, Alexandros (My University, 2013)
Continuous topography from Digital Elevation Model (DEM) data is frequently segmented into terrain classes based on local morphological characteristics of terrain elevation, e.g., local slope gradient and convexity. The resulting classes are often used as proxies for the average shear wave velocity up to 30 m, and the determination of ground types as required by the Eurocode (EC8) for computing elastic design spectra. In this work, we investigate the links between terrain related variables, particularly slope gradient, extracted for the area of Greece from the Shuttle Radar Topography Mission (SRTM) 30 arc second global topographic data available from the United States Geological Survey (USGS), with: (a) the global terrain classification product of Iwahashi and Pike (2007) in which 16 terrain types are identified for the same spatial resolution, and (b) information on geological units extracted at the same resolution from the geological map of Greece at a scale of 1/500000 as published from the Institute of Geology and Mineral Exploration (IGME). An interpretation of these links is presented within the context of understanding the reliability of using geology, slope and terrain classes for site characterizations of earthquake risk in a high seismicity area like Greece. Our results indicate that slope is a somewhat biased proxy for solid rocks, whereas in Alluvial deposits the distance to and type of the nearest geological formation appears to provide qualitative information on the size of the sedimentary deposit. © 2013 SPIE.
Keywords: Earthquake Risk; Eurocode; GIS; Terrain Classification